Leveraging epigenetic aberrations in the pathogenesis of endometriosis: from DNA methylation to non-coding RNAs - Erraji, Hajar; El Ghanmi, Adil; Louanjli, Noureddine; Benahmed, Mohamed; El Mansouri, Fadoua; Zarqaoui, Mohammed; Ghazi, Bouchra (Frontiers in Genetics, 2025)
Endometriosis is highly underdiagnosed and undertreated gynecological disorder, with diagnosis often delayed by 8–12 years. This delay can have serious consequences including infertility. Currently, the gold standard for endometriosis diagnosis and treatment is laparoscopy, an invasive surgical intervention. The molecular mechanisms underlying the onset of endometriosis are yet unclear, but it is assumed that epigenetic modifications are an important contributor in the etiopathology of the disease. Given that, dissecting the features of epigenetic aberrations underlying endometriosis can be a crucial step toward developing early and accurate non-invasive diagnostic tools. Accurate and timely diagnosis of endometriosis can significantly reduce healthcare costs, and enhance women’s social wellbeing. Epigenetic modifications especially DNA methylation, micro-RNAs and long-RNAs, hold promise as potential biomarkers for the early diagnosis of endometriosis. This review underscores the innovative potential of epigenetic mechanisms as early biomarkers for endometriosis diagnosis. We summarize and critically discuss recent findings and epigenetic modifications role in endometriosis pathophysiology, from DNA methylation and histone modifications to non-coding RNAs in different tissues.